2019
DOI: 10.3390/ijerph16030355
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stress as a Predictor of Partnership Relation Quality in Polish Mothers of Preterm-Born Children

Abstract: The aim of the study was to identify whether perceived stress and significant life changes are related with partnership relation quality in mothers of preterm-born children. The study group consisted of 260 women, who gave a preterm birth. In most cases the delivery took place in the 34–36th week of pregnancy. The research consisted of two phases. Phase 1 was carried out in the Department of Obstetrics at the Medical University of Gdansk in the neonatal period (2–3 days after birth). Phase 2 was carried out in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
0
6
1
Order By: Relevance
“…In contrast with other studies, our participants experienced the strengthening of marital relationships (Kim, 2018). Bidzan and Lutkiewicz (2019) demonstrated that stressful situations are not associated with the quality of the relationship. Similar to the findings of other studies, social support tends to pay more attention to mother than father, leading to the disconnection of father from care of extremely preterm infant (Kim, 2018).…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast with other studies, our participants experienced the strengthening of marital relationships (Kim, 2018). Bidzan and Lutkiewicz (2019) demonstrated that stressful situations are not associated with the quality of the relationship. Similar to the findings of other studies, social support tends to pay more attention to mother than father, leading to the disconnection of father from care of extremely preterm infant (Kim, 2018).…”
Section: Discussioncontrasting
confidence: 99%
“…Additional biomarkers responsible for the transfer of psychological stress could also be included, such as oxidative stress, cytokines, gut microbiota, serotonin/tryptophan, reactive oxygen species (ROS), and catecholamines [51]. Further research is also needed to analyze the effectiveness of psychological interventions in reducing anxiety, depression [52], and chronic stress and their subsequent impact on IVF treatment outcomes and pregnancy [14,30,53].…”
Section: Discussionmentioning
confidence: 99%
“…When considering issues regarding pregnancy and childbirth, it is important to consider perinatal depression. This disease affects about 10-15% of women [19][20][21][22][23][24]. Therefore, this issue was taken into account in our research and depression was a controlled variable in this study.…”
Section: Methodsmentioning
confidence: 99%